The ultimate meal planning for one cookbook : 100+ easy, affordable, and low-waste (high-taste!) recipes made just for you - Jaggers, Kelly (Ultimate for one., 2024)
"Meal planning for one can feel daunting...especially if you want to avoid tons of leftovers and food waste while still making delicious single-serving meals. The good news is that The Ultimate Meal Planning for One Cookbook is here to help with easy-to-use meal plans and over 100 recipes that are designed for meal planning for one. This book allows you to make over 100 delicious, one-to-two-serving recipes for every meal from breakfast to dinner and everything in between. And, not only will you find tasty recipes designed for one, you'll also learn to use them to design your own weekly meal plans. Learn how to avoid eating the same old leftovers over and over throughout the week, how to utilize your ingredients as much as possible so nothing goes to waste, and to enjoy delicious versions of your favorite dishes, no matter the occasion. Whether you live alone or are just searching for the perfect meal for yourself, cooking solo need never be boring (or repetitive and wasteful!) again"--